A control strategy for adaptive absorber based on variable mass. (July 2015) - Gao, Qiang; Han, Ning; Zhao, Yanqing; Duan, Chendong; Wang, Wanqin
Abstract: The tuned vibration absorber (TVA) has been an effective tool for vibration control. However, the application of TVA can cause resonance of the primary system and increase its vibration when the absorber is mistuned. In this paper, a novel control strategy based on adaptive tuned vibration absorber (ATVA) of variable mass is proposed to reduce the resonance of the primary system. Unlike most ATVAs suggested by other researchers which adjust the absorber natural frequency by changing the stiffness, the variable mass ATVA varies its natural frequency by changing absorber mass to match the excitation frequency. Some simulations and experiments were conducted to test the performance of the control strategy. The results show that the proposed control plan can widen the frequency bandwidth of the absorber, as well as suppress the resonance of the primary system significantly. This implies that the work is useful for practical applications of ATVA.